Accessible Mannitol‐Based Amphiphiles (MNAs) for Membrane Protein Solubilisation and Stabilisation. Issue 21 (13th April 2016) - Hussain, Hazrat; Du, Yang; Scull, Nicola J.; Mortensen, Jonas S.; Tarrasch, Jeffrey; Bae, Hyoung Eun; Loland, Claus J.; Byrne, Bernadette; Kobilka, Brian K.; Chae, Pil Seok
Abstract: Integral membrane proteins are amphipathic molecules crucial for all cellular life. The structural study of these macromolecules starts with protein extraction from the native membranes, followed by purification and crystallisation. Detergents are essential tools for these processes, but detergent‐solubilised membrane proteins often denature and aggregate, resulting in loss of both structure and function. In this study, a novel class of agents, designated mannitol‐based amphiphiles (MNAs), were prepared and characterised for their ability to solubilise and stabilise membrane proteins. Some of MNAs conferred enhanced stability to four membrane proteins including a G protein‐coupled receptor (GPCR), the β2 adrenergic receptor (β2 AR), compared to both n ‐dodecyl‐d ‐maltoside (DDM) and the other MNAs. These agents were also better than DDM for electron microscopy analysis of the β2 AR. The ease of preparation together with the enhanced membrane protein stabilisation efficacy demonstrates the value of these agents for future membrane protein research. Abstract : Membrane proteins : A novel class of mannitol‐based amphiphiles (MNAs; see scheme) was developed and, of these MNAs, MNA‐C13 displayed the most favourable behaviour in solubilising and stabilising multiple membrane proteins. This agent was also promising in electron microscopy analysis of a GPCR.